Effects of Recurrent Mild Traumatic Brain Injuries on Incidence, Severity, and Recovery of Concussion in Young Student-Athletes. Issue 4 (July 2021) - Hannah, Theodore C.; Spiera, Zachary; Li, Adam Y.; Durbin, John; Dreher, Nickolas; Ali, Muhammad; Marayati, Naoum Fares; Gometz, Alex; Lovell, Mark; Choudhri, Tanvir
Abstract : Objective: To examine the effects of recurrent concussions on the incidence, severity, and recovery of significant neurocognitive dysfunction (SND) in young athletes. Setting: Various US youth sports organizations that utilize Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) for baseline and postinjury concussion testing. Participants: Data from 11 563 ImPACT baseline evaluations of US student-athletes aged 12 to 22 years were separated into 2 cohorts: subjects reporting 2 or more previous concussions (PC; n = 976 baseline evaluations) at baseline and a control group reporting zero previous concussions (CT; n = 7743 baseline evaluations). Subjects reporting 1 prior concussion were excluded. Design: Retrospective cohort. Main Measures: Differences in SND incidence, severity, and recovery between the 2 cohorts were assessed using chi-squared tests, t tests, survival analyses, and multivariate regressions. Results: The PC cohort had a higher incidence of head injury leading to ImPACT (436.7 per 1000 person-years vs 194.4 per 1000 person-years, P < .0001) and a higher incidence of SND (140.4 vs 71.8, P < .0001) than controls. However, the Severity Index (SI) demonstrated that SND severity was lower in the PC group (7.55 vs 8.59, P = .04). Adjusted analyses similarly demonstrated that the PC cohort had increased SND incidence (odds ratio = 1.93; 95% CI, 1.61 to 2.31; P < .0001), decreased SI (β = −1.37; 95% CI, −2.40 to −0.34; P = .009), and equivalent recovery (hazard ratio = 0.98; 95% CI, 0.76 to 1.72; P = .90). Conclusion: Participants with a history of concussion have a higher incidence of SND but present with lower severity SND, which may be a result of increased concussion education or symptom awareness. Recurrent concussion has no significant impact on acute neurocognitive recovery. Together, these results provide evidence against the supposition that a history of concussion increases the severity of future SND. Abstract : Supplemental Digital Content is Available in the Text.